MANAGING THE SOCIAL AND CULTURAL SPHERE OF A MODERN SMALL CITY - Zhelnina, E.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The article is devoted to the study of the process of managing the socio-cultural sphere of a modern small city. The socio-cultural sphere occupies one of the main places in the life of the city. It affects the ongoing social processes and phenomena, largely determines and organizes the life of the municipality as a whole. The main source of empirical data was an expert survey conducted by the author in December 2019. Empirical data were obtained in December 2019 during the applied sociological study "management of the socio-cultural sphere of a small city". The object of empirical research is representatives of the Russian small city administration responsible for the implementation of urban socio-cultural policy. Among the main conclusions, it can be noted that the main difficulties in managing the socio-cultural sphere of a modern small city are reduced to insufficient funding. Among other things, insufficient financial support makes it difficult to predict the existence of an urban socio-cultural environment. In addition, the positive aspect is also the confidence of the employees of the Department of culture that this small city has a high level of socio-cultural competitiveness in comparison with nearby localities. In our opinion, this point of view is an additional incentive to success. Based on the data obtained, scientifically and empirically based practical recommendations were prepared.